An intelligent agent system for managing heterogeneous sensors in dispersed and disparate wireless sensor network. (2018) - Lee, Yong Jin; Trevathan, Jarrod; Atkinson, Ian; Read, Wayne
Wireless sensor networks (WSNs) employ middleware solutions to coordinate their sensors and provide web services for managing data. Adding/configuring a new or existing sensor requires modification to the middleware and web service. To integrate hundreds of sensors with different capabilities, a system needs to support all the encodings, models and services for registering, tasking and querying sensors. We present an intelligent agent, which provides automatic semantic-based registration/configuration in a large-scale sensor observation system. The agent can react to any changes internally/externally made (i.e., adding a new sensor or sending a task request to sensors/support systems). The agent makes a 'smart' decision on which system function to use by integrating a semantic representation of sensor network data including middleware and web service specifications and applying logical rules to the knowledge-base. The agent's operation is demonstrated using two real-world systems represented in RDF using a domain ontology that extends the W3C SSN-XG ontology.